Growth, linear, nonlinear optical, electronic and mechanical studies of urea-phosphoric acid crystals. (2022) - Vinothkumar, P.; Shalini, D.; Antony Suresh, A.; Murugasen, Priya
Abstract: An organic single crystal of the nonlinear optical Urea Phosphoric acid (UP) with 14 × 5 × 4 mm 3 was grown by low temperature solution growth technique. X-ray diffraction analysis confirmed the orthorhombic crystallographic structure of UP crystal with space group Pbca . High-resolution X-ray diffraction was used to examine the crystalline perfection of the Urea Phosphoric acid (UP) single crystal. The optical transmittance and refractive index of the Urea Phosphoric acid (UP) single crystal was studied by UV–vis spectral analysis. The results confirmed that the UP crystals had good transparency throughout the visible region. The mechanical behaviour of the Urea Phosphoric acid (UP) crystal was assessed by Vickers microhardness measurements. The hardness measurements revealed the reverse indent effect (RISE). The refractive index of the Urea Phosphoric acid (UP) was measured. The threshold value of laser damage of Urea Phosphoric acid (UP) crystal was determined by Nd: YAG laser and found to be 3.2 GW/cm 2 . The third-order NLO coefficients of the Urea Phosphoric acid (UP) crystal was also studied. The Results were discussed in detail.